Response dynamics of event-based prospective memory retrieval in mouse tracking. - Hicks, Jason L.; Spitler, Samantha N.; Papesh, Megan H. (Memory & Cognition, 2019)
Prospective memory (PM) is typically measured using keypresses in laboratory paradigms, which therefore assess only discrete, stage-like processes. In the present study we manipulated focal and nonfocal PM cue conditions, as well as participants' focus on different aspects of the PM/ongoing task set, using the methodology to capture dynamic computer mouse movements. The software captured mouse trajectories during lexical decisions and PM responses. We replicated many findings typical in the PM literature, including the accuracy advantage for focal over nonfocal conditions and longer ongoing-task response times for nonfocal conditions. Participants' movement trajectories during PM responses revealed evidence for both spontaneous-retrieval and strategic-monitoring processes in focal and nonfocal PM retrieval conditions. During trials suggestive of spontaneous retrieval, mouse trajectories initially went toward the typical ongoing-task response but turned mid-trajectory toward the PM response field on the opposite side of the computer screen. In nonfocal conditions, these trajectory reversals had a wider arc and took longer to complete, reflecting the likely greater retrospective retrieval requirements of nonfocal conditions. Regarding what are more likely to be strategic-monitoring processes, a significant portion of responses traveled directly to the PM response field, as though people were prepared to make such a response.